THE USE OF REALIA IN TEACHING SPEAKING SKILLS FOR THE FOURTH GRADES AT SDN KARANGANYAR GUNUNGKIDUL - Anisa Fajariyah; Yuyun Yulia (JELLT (Journal of English Language and Language Teaching), 2019)
This study aimed to describe: 1) the implementation of realia to teach speaking skill of the fourth graders of SDN KaranganyarGunungkidul and 2) the media that was used to motivate students to actively engage in teaching speaking skill of the fourth graders of SDN KaranganyarGunungkidul. This study is a classroom action research. The subjects of this study were the fourth graders of SDN KaranganyarGunungkidul which consisted of 32 students. The research was conducted in two cycles containing three stages namely exploration, elaboration, and confirmation. The data were collected through observation, interview, field note, and document. The result showed the implementations of using realia were successful in motivating the students to speak. In the cycle one, the realia were used as the object in introducing vocabulary in exploration stage asthe aids in describing object about things in the classroom. As a result of using realia, the students were motivated to speak and able to describe the things in the classroom. In the cycle 2, the realia were still used as the object in introducing vocabulary in exploration stage and in elaboration stage. The realia werethe aids in describing objects about family. As a result, the students were motivated to speak and able to describe about their family. Realia that can be used to motivate the students to actively engage in teaching speaking were real object and puppet.